Typical and impaired processing in morphosyntax - Torrens, Vincent (Language acquisition and language disorders,, 2020)
"The present volume deals with research on language processing and disorders. It covers topics ranging across syntax processing, bilingualism, lexical processing and language disorders. The articles presented in this volume cover a number of linguistic phenomena, including the following: subject control, object control, raising, unaccusatives and unergatives, noun gender, relative clauses, A' movement, filler-gap dependencies, ditransitives, prepositional phrases, argument structure, personal pronouns, anaphora, long distance extraction and inflectional morphology. The research presented in this volume covers typical language processing, child developmental language disorders, adult neurodegenerative disorders and neurological bases of typical or impaired brains. Papers in this collection use a variety of experimental methods, such as eye tracking, reaction times, Event Related Potentials, picture selection tasks, sentence elicitation and picture matching tasks. This book can be useful for linguists, speech therapists, and psycholinguists working on the processing of morphosyntax"--